Analysis of Auto Car Jack - M. M., Noor; K., Kadirgama; M. M., Rahman (2010)
Side road emergency is always a common headache especially during the tire punctured. This paper discussed the development of the car jack for emergency usage with using internal cigarette lighter power (12volts). The automatic easy car-jack utilized this power source to save individuals internal energy. Gear ratio was used to increase the lifting power. The car jacker was developed utilizing the Solidworks® and analyzed using Finite Element Analysis to check safety factor and force acting. The car jacker tested on real car and it proven it can be used commercially.